Rural Development and Living Conditions Index and the municipalities of Arapongaand Tombos, MG: the perception of family farmers - Reis de Oliveira, Brasilina Elisete; Lee Ribeiro, Francis (Universidade Federal Rural do Rio de Janeiro, 2016)
The paper presents the results of a research about the perceptions of family farmers regarding their living conditions in two towns of Minas Gerais, Tombos and Araponga. It was used the Índice de Condições de Vida (ICV). The results indicate that farmers have a good evaluating of their life conditions, despite claim specific public policies to the development of these areas. It was also perceived the need of reorganization of social representations, considered by them as important allies for the strengthening of family agriculture, as well as for the rural development process, but which present poor performance.